THE ROLE OF MBKM IN EDUCATION POST-COVID-19 PANDEMIC - Sukma Dewi Hapsari; Nurul Hidayah Puji Lestari; Nurjannah Nurjannah; Suratno Suratno (Proceeding International Seminar of Islamic Studies, 2022)
The Covid-19 pandemic has hurt all sectors. Even the bad impact is still felt even though it has entered the post-Covid-19 era. This is especially true in the field of education. During 2 years of online learning, many obstacles were experienced, then when face-to-face learning started again, the problems faced were more severe than distance learning. This study aims to analyze the role of Merdeka Belajar Kampus Merdeka (MBKM) which for 1 year has been the flagship program to educate the nation's children during and after Covid-19. This research approach is a kind of qualitative literature.The results showed that the Merdeka Belajar Kampus Merdeka (MBKM) program had many roles to revive the spirit of learning for students. Not only that, but this program also involves contributions from students which will later be useful for entering the world of work, and provide opportunities for students to choose the courses they will take. Implementation of the MBKM curriculum to answer the challenges of technological development, with an OBE (Outcome Based Education), based learning system so that graduates focus on learning outcomes that are aligned with scientific disciplines.Keywords: Covid-19, Face to Face Learning, MBKM, Online Learning